2000
DOI: 10.1152/ajplung.2000.279.3.l468
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant metabolism in SP-D gene-targeted mice

Abstract: Mice with surfactant protein (SP)-D deficiency have three to four times more surfactant lipids in air spaces and lung tissue than control mice. We measured multiple aspects of surfactant metabolism and function to identify abnormalities resulting from SP-D deficiency. Relative to saturated phosphatidylcholine (Sat PC), SP-A and SP-C were decreased in the alveolar surfactant and the large-aggregate surfactant fraction. Although large-aggregate surfactant from SP-D gene-targeted [(-/-)] mice converted to small-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 36 publications
7
91
0
1
Order By: Relevance
“…The spots were visualized with iodine vapor, scraped, and assayed for phosphorus content. Surfactant proteins in BALF were analyzed by Western blot after SDS-PAGE (11,18).…”
Section: Methodsmentioning
confidence: 99%
“…The spots were visualized with iodine vapor, scraped, and assayed for phosphorus content. Surfactant proteins in BALF were analyzed by Western blot after SDS-PAGE (11,18).…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Studies with SP-D knockout mice have also indicated a role of SP-D in the regulation of surfactant lipid homeostasis. 12 Furthermore, Brinker and colleagues 13 found that human SP-D binds to immature bone marrow-derived dendritic cells (DC) in vitro in a dose-, carbohydrate-and calcium-dependent manner, enhancing the phagocytic uptake of Escherichia coli and the antigen presentation to T cells.…”
Section: Introductionmentioning
confidence: 99%
“…SP-D single deficient mice show altered lung pathology consistent with emphysema, abnormalities of alveolar macrophages, as well as of type II cells and an increased alveolar surfactant pool size (Botas et al, 1998;Ikegami et al, 2000a;Wert et al, 2000). SP-A single deficient mice lack tubular myelin but have no obvious changes in surfactant metabolism under resting conditions (Korfhagen et al, 1996;Ikegami et al, 1997).…”
mentioning
confidence: 99%